To the Moon and Back - Kingsbury, Karen; Heyborne, Kirby; LaVoy, January ([New York] : Audioworks, imprint of Simon & Schuster Audio, 2018)
Struggling to help the smitten son of an Oklahoma City bombing victim find the daughter of another bombing victim, Ashley tries to get her skeptical husband to understand why she feels strongly compelled to get involved.
Keywords: Oklahoma City Federal Building Bombing, Oklahoma City, Okla., 1995 -- Fiction; Disaster victims -- Fiction; Man-woman relationships -- Fiction; Audiobooks; FICTION / Christian / Romance; FICTION / Christian / General; FICTION / Religious; Audiobooks; Christian fiction; Romance fiction; Religious fiction